Recent Trends in Novel Drug Delivery for Treatment of Type I and Ii Diabetes Mellitus - Namdev, Shrishti; Jamkar, Preeti; Mandlik, Satish; Gujar, Kishore (Asian Journal of Pharmaceutical Research and Development, 2014)
Around 200 million people worldwide are found to be affected by Diabetes mellitus (DM). DM is a metabolic disorder which occurs due to reduced insulin action and/or insulin secretion in the body. With the progression of disease, pathological changes like nephropathy, retinopathy and cardiovascular complications start occurring in the body. DM is mainly categorized into 2 types: type 1 DM and type 2 DM. Type 1 is generally treated through insulin replacement therapy. Type 2 DM is treated with oral hypoglycemics. Insulin administration is essential for type 1 patients while it is required at later stage by the patients of type 2. Current insulin delivery system is invasive approach. Several non-invasive approaches for insulin delivery are being pursued by pharmaceutical companies to reduce the pain, and hypoglycemic incidences associated with injections in order to improve patient compliance. Although the availability of new agents for treatment of type 2 DM, oral hypoglycemic are base of therapy, because they are relatively economical and well tolerated. A well designed controlled drug delivery system can overcome some of the inconvenience of conventional therapy and enhance the therapeutic efficacy of drug. These newer generations of drug delivery systems are advantageous over conventionally available drug delivery systems. This review article discusses the various non-invasive techniques for insulin administration and also highlights various novel drug delivery systems that have been investigated by different researchers for achieving sustained and controlled drug delivery of oral hypoglycemics and for overcoming the limitations related with conventional dosage forms of oral hypoglycemics.